Demands and satisfaction for family doctor contracted services in Tianjin City: A survey based on Kano model - Wei Tingting; Zhang Zhibo; Li Ruolan; Liu Pei; Liu Ying; Pan Liping; Jia Jie; Zhang Na; Bian Bo (Chinese General Practice Journal, 2025)
Background: Family doctor contracted services have been widely implemented across China, yet challenges remain in improving coverage and service quality. Objective: This study analyzes the demands for family doctor contracted services across different age groups and contracting status in Tianjin communities, using the Kano model, and evaluates satisfaction among residents who have signed with family doctors. Methods: A cluster stratified sampling method was employed to distribute questionnaires to residents in six communities across ten districts of Tianjin City from October 2023 to January 2024. Data were collected via face-to-face interview and interviewers assisted completing questionnaire for the participants. The Kano model was used to analyze service demands, and satisfaction was also assessed. Results: A total of 600 questionnaires were completed. Kano model analysis classified service attributes as follows: Must-be Attributes (community health education, common disease diagnosis and treatment, additional 5 % outpatient reimbursement, long-term prescriptions), One-dimensional Attributes (referral services, comprehensive health assessments), Attractive Attributes (medication assessment, personalized annual health plans, home bed service, home visits, family lifestyle counseling), and Indifferent Attributes (health knowledge and skill training, electronic health records). Significant variations in demands were observed by age and contracting status. The top satisfaction scores for participants who have signed with family doctors were: additional 5 % outpatient reimbursement (4.09 ± 1.14), long-term prescriptions (4.03 ± 1.14), electronic health records (3.55 ± 1.20), common disease diagnosis and treatment (3.29 ± 1.40), and community health education (3.27 ± 1.20). The lowest scores were for health knowledge and skill training (3.14 ± 1.24), medication assessment (3.12 ± 1.26), referral services (3.11 ± 1.02), home bed service (2.97 ± 1.30), and home visits (2.94 ± 1.21). Conclusion: The study identifies key service attributes that influence satisfaction and highlights significant variations in demands across age and enrollment groups.